PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Sanky Novia Dwi Martha; Anggi Putri Kusuma Wardini; Wiwin Sukiati; Rima Dwijayanti (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
This study analyzes the effect of Corporate Social Responsibility (CSR) and company size on financial performance as proxied by Return on Assets (ROA). The study employs a quantitative approach using panel data regression on companies included in the LQ45 index listed on the Indonesia Stock Exchange during the 2019–2022 period. The results indicate that CSR does not have a significant effect on financial performance, while company size has a significant effect. Simultaneously, CSR and company size have a significant effect on financial performance. The coefficient of determination shows that 19.3% of financial performance variation is explained by the independent variables, while the remaining 80.7% is explained by other factors outside the model